2016
DOI: 10.2147/ijn.s106912
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nickel oxide nanoparticles induces pulmonary inflammation through NLRP3 inflammasome activation in rats

Abstract: With recent advances in the manufacture and application of nickel oxide nanoparticles (NiONPs), concerns about their adverse effects on the respiratory system are increasing. However, the underlying cellular and molecular mechanisms of NiONP-induced pulmonary toxicity remain unclear. In this study, we focused on the impacts of NiONPs on pulmonary inflammation and investigated whether the NLRP3 inflammasome is involved in NiONP-induced pulmonary inflammation and injury. NiONP suspensions were administered by si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 51 publications
4
33
0
1
Order By: Relevance
“…In these studies, we showed an ability of these NPs to cause DNA damage in lung cells, results in line with other studies (Latvala et al 2016;M'Bemba-Meka, Lemieux, and Chakrabarti 2005). Furthermore, inflammatory effects of NiO NPs have been shown both in vitro (Capasso, Camatini, and Gualtieri 2014) and in vivo (Nishi et al 2009;Gillespie et al 2010;Morimoto et al 2010;Cao et al 2016;Bai et al 2017). Yet, no studies have elucidated whether NiO NP-induced inflammation can cause genotoxicity.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In these studies, we showed an ability of these NPs to cause DNA damage in lung cells, results in line with other studies (Latvala et al 2016;M'Bemba-Meka, Lemieux, and Chakrabarti 2005). Furthermore, inflammatory effects of NiO NPs have been shown both in vitro (Capasso, Camatini, and Gualtieri 2014) and in vivo (Nishi et al 2009;Gillespie et al 2010;Morimoto et al 2010;Cao et al 2016;Bai et al 2017). Yet, no studies have elucidated whether NiO NP-induced inflammation can cause genotoxicity.…”
Section: Introductionsupporting
confidence: 90%
“…Following 18 h exposure, we noted increased IL-1a and IL-1b, in line with some previous studies. One study demonstrated, for example, that NiO NP exposure induced pulmonary inflammation by activating the NLRP3 inflammasome (in vivo and in vitro) and an increased secretion of IL-1b and IL-18 was observed (Cao et al 2016). In another study the expression of cytokines in the lung tissue and BALF was analyzed following intratracheal instillation of NiO NPs in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of both cytosolic and extracellular danger signals, such as mtDNA and ATP, contributes to the priming and activation of the NLRP3 inflammasome. As such, numerous studies link TiO 2 , Ag, SiO 2 , and NiO NPs to NLRP3 inflammasome formation through the production of ROS, the release of endogenous danger signals such as mtDNA, ATP, and cathepsin B, and via the NPs themselves . Aside from inducing the cell damage necessary to expose danger signals, NP‐induced oxidation of DAMPs, such as mtDNA, enhances recognition by NLRP3 …”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
“…The activation of NLRP3 and subsequent release of IL‐1β has been implicated as the direct mechanism by which TiO 2 NPs worsened colitis symptoms in a dextran sulfate sodium (DSS)‐induced colitis mouse model; the administration of TiO 2 NPs to NLRP3 knockout mice did not produce the same colitis pathology as in wild‐type mice. Similarly, the administration of NiO NPs to RAW246.7 macrophages induced caspase‐1 activity and NLRP3 inflammasome formation, whereas this activity was inhibited in NLRP3‐knockdown macrophages . Certain studies have indicated that NP‐induced NLRP3 inflammasome formation was dependent on ROS production and the endogenous danger signals resulting from oxidative stress, whereas others implicate more specific pathways, such as SR‐B1 signaling and lysosomal destabilization/cathepsin B release in NLRP3 inflammasome activation …”
Section: Np Exposure Leads To Release Of Endogenous Danger Signalsmentioning
confidence: 99%
See 1 more Smart Citation